ISLAMIC REFORMIST MOVEMENT OF HAJI SULONG ABDUL KADIR IN ISLAMIC EDUCATION INSTITUTIONS IN THAILAND’S SOUTHERN BORDER - Joseph Chinyong Liow; Moch Khafidz Fuad Raya (Jurnal Pendidikan Islam, 2020)
The development of Islamic education in southern Thailand has been in the spotlight of researchers in the last decade in efforts to establish a national education, although this study is still less attractive. The existence of Pondok schools as Islamic educational institutions is considered to have mobilized separatist movements and the authority of traditional Malay Muslim elites to fight for territory. The existence of the Malay rulers with their authority in the fields of religion and culture made traditional Islamic education deeply rooted in the southern Thailand region. Muslims in the southern province are allegedly a monolithic entity whose existence constructs the institutionalization of Thailand as a state, thus opening up space for separatist seeds that emerge from Islamic educational institutions. The existence of Islamic reformers such as Haji Sulong Abdul Kadir is strong evidence that his movement is treading the religious and cultural field in the process of reviving the institutionalization of Islamic education in Southern Thailand. The establishment of Madrasah al-Ma'arif al-Wataniah Fatani as a forum for Haji Sulong Abdul Kadir to fight for reforms in Islamic education institutions, despite strong opposition from the state and the authority of the traditional Malay Muslim elite but ultimately the principles of reform were realized even though the reformers had died and the madrasa was closed.